A case of maternal uniparental disomy of chromosome 20 detected by noninvasive prenatal test of 1,000 high-risk pregnancies - Cha, Dong Hyun; Lee, Junnam; Jeon, Young-Joo; Jung, Yong Wook; Jang, Ja-Hyun; Lee, Taeheon; Cho, Eun Hae (Journal of genetic medicine, 2017)
Chromosomal loss in trisomy (trisomy rescue) to generate a disomic fetus can cause confined placental mosaicism and/or feto/ placental mosaicism. After trisomy rescue event, there is a risk of fetal uniparental disomy (UPD). Noninvasive prenatal test (NIPT) reflects the genomic constitution of the placenta, not of the fetus itself. Feto-placental discrepancy can therefore cause false-positive (trisomy) NIPT results. These discordant NIPT results can serve as important clues to find UPD associated with confined placental mosaicism. We report a case with maternal UPD of chromosome 20, detected by NIPT of 1,000 high-risk pregnancies, carried out for detecting chromosomal abnormalities in Koreans. KCI Citation Count: 0